2009
DOI: 10.1016/j.jcrysgro.2009.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the annealing process on the microstructure of La2Zr2O7 thin layers epitaxially grown on LaAlO3 by metalorganic decomposition

Abstract: were varied to establish their influence on the microstructure of the LZO layers. XRD and TEM were used for sample characterisation. The epitaxial pyrochlore phase was obtained for annealing temperatures higher that 850°C whatever the other annealing conditions. However, the film microstructure, in particular, nanovoids shape and size, is strongly dependent on heating ramp and pressure during annealing. When using low heating ramp, percolation of voids creates diffusion channels for oxygen which are detrimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…3 for a sample before the oxidation treatment. The LZO grains, well visible from top, have size in the range of 20-50 This phenomenon has already been observed several times by others [12]- [14] and curiously does not impede the development of ahigh quality textured layer (in-plane 7.5 , out of plane 6-10 depending whether the measurement was done along rolling direction, RD, or along transverse one, TD). Up to now, the origin of the pores is unclear but is probably associated with the gas emitted during the pyrolysis step.…”
Section: B Microstructuresupporting
confidence: 57%
See 1 more Smart Citation
“…3 for a sample before the oxidation treatment. The LZO grains, well visible from top, have size in the range of 20-50 This phenomenon has already been observed several times by others [12]- [14] and curiously does not impede the development of ahigh quality textured layer (in-plane 7.5 , out of plane 6-10 depending whether the measurement was done along rolling direction, RD, or along transverse one, TD). Up to now, the origin of the pores is unclear but is probably associated with the gas emitted during the pyrolysis step.…”
Section: B Microstructuresupporting
confidence: 57%
“…4(b), non-oriented is mixed with a rather large NiO area in a two phases range as predicted by the phase diagram [12]. The NiO layer extends up to 500-600 nm below the LZO layer, imaged in grey on top of the cross section.…”
Section: B Microstructurementioning
confidence: 82%
“…In previous studies, we demonstrated that a fast heating rate was necessary during the crystallization process [20] but we stopped our study of the annealing temperature at 960°C, because we were mainly studying this effect on the porosity of the LZO layer. We did not pay a closer attention to the surface morphology.…”
Section: B the Effect Of Annealing Temperaturementioning
confidence: 99%
“…Based on examples of LZO microstructure found in the literature and the results presented in this paper, we want to draw the attention to the influence of some parameters important to the LZO growth. Other researchers have argued that the escaping of carbon-rich gases are creating nanovoids and that nanovoid formation is intrinsic to chemical solution deposition methods [16,30].…”
Section: Nanovoid Formationmentioning
confidence: 99%
“…That nanovoids are a CSD typical phenomenon, could be contested because nanovoids have not only been observed in CSD prepared LZO layers [16,30,31]), but also in electrodeposited Gd 2 Zr 2 O 7 films [32]. The relationship between deposition technique and the presence of nanovoids should therefore be reconsidered.…”
Section: Nanovoid Formationmentioning
confidence: 99%